Improved quality of Kambing Kacang sexing frozen semen with the addition of green tea extract - Suprayog, Tri Wahyu; Susilowat, Suherni; Hernawat, Tatik; Hafidha, Farah Ghifara; Wening, Citra Ayu; Purnawan, Ahmad Budi (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: The objective of this study was to determine the effect of adding various doses of green tea extract to the semen of Kacang goats during the sexing process on motility, viability, membrane integrity, malondialdehyde (MDA), and deoxyribonucleic acid (DNA) fragmentation. Materials and Methods: It started with the containment of the semen of the Kacang goat, followed by macroscopic and microscopic examinations. If the semen was considered viable, a diluter that had been added with various doses of green tea extract would be added to the semen. After that, sexing was carried out using the percoll gradient density medium. Next, the sexed semen was cryopreserved in liquid nitrogen. Then, an examination of motility, viability, membrane integrity, MDA, and DNA fragmentation was conducted. Result: There was a significant difference between the control and treatment (p ≤ 0.05). The highest result was obtained in the treatment of adding 0.05 mg of green tea extract/100 ml of Andromed®. Conclusion: The addition of green tea extract can improve the quality of the sexed semen of the Kacang goat after it has been cryopreserved. J. Adv. Vet. Anim. Res., 9(3): 412–418, September 2022 http://doi.org/10.5455/javar.2022.i609